2019
DOI: 10.1111/hsc.12894
|View full text |Cite
|
Sign up to set email alerts
|

“Growing Old is not for the Weak of Heart”: Social isolation and loneliness in Muslim immigrant older adults in Canada

Abstract: The increase in global migration means more immigrants are ageing in host countries with unique experiences and needs. Muslim immigrants in Canada are from diverse ethnocultural communities and experience unmet health and social needs in older age. A community‐based participatory research project was conducted in Alberta, Canada, in 2017–2018 to understand the experiences and needs of healthy ageing in this population. A community advisory committee participated in all phases of the research project including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 29 publications
3
49
0
Order By: Relevance
“…Therefore, she concluded that these sites can help to overcome feelings of loneliness and isolation. In a similar vein, a very recent qualitative study concluded that sites such as Facebook or video chats, via Skype, for example, can help to overcome social isolation among Muslim immigrant older adults in Canada [8]. In sum, the findings are mixed.…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, she concluded that these sites can help to overcome feelings of loneliness and isolation. In a similar vein, a very recent qualitative study concluded that sites such as Facebook or video chats, via Skype, for example, can help to overcome social isolation among Muslim immigrant older adults in Canada [8]. In sum, the findings are mixed.…”
Section: Main Textmentioning
confidence: 99%
“…To keep their health is quite important not only for older people living outside of their native country but also every older person. However, once they have chronic diseases, they face many barriers such as language, difference of culture, and discrimination [29,30]. Since they are a minority compared with native older people, a supportive system is needed from their country.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the loneliness of older migrants with that of native-born peers in the country of destination are limited in their explanation of the role of general risk factors such as poor health and low socio-economic position. The benefit of studies exploring variation in loneliness within the group of older migrants is that they are able to examine the impact of migrant-specific factors such as language mastery (Cela and Fokkema 2017 ; Gautam et al 2018 ), feelings of discrimination (Salma and Salami 2020 ), and sense of belonging to the mainstream society (Gautam et al 2018 ; Klok et al 2017 ). As these factors affect social interactions, it is not surprising that their observed effects on loneliness are in the expected direction: the less proficiently older migrants master the destination language, the more often they experience ethnic discrimination, and the less strongly they feel connected to the wider society, the lonelier they are.…”
Section: Transnational Belonging: Resource Versus Stressormentioning
confidence: 99%